Relation between Mass, Angular Momentum and Spin Parameter of Black Holes (Global Journal of Science Frontier Research, 2020)
, which concludes that the angular momentum may be regarded as additional characterizing parameter of black holes.
Keywords: angular momentum; spin parameter and surface gravity